Virtual teams definition, advantages and disadvantages of using such kind of team and their difference from traditional teams (Вестник КазНУ. Серия Экономическая, 2016)
This article is an overview of involvement virtual team into projects. It gives the definition of this notion; moreover, it contains basic criteria, when such kind of team is involved into project and general classifica-tion of virtual teams. The pros and cons of virtual team, which are de-scribed here, may help project manager to estimate all risk while form-ing the project team. There are several tasks, which is set to the project manager when he or she initiate the project one of them is set the team. At the same time project manager faced with the problem, where he or she can take the human resources. This problem can occur because of the matrix organizational system in the company, where the staff performs the operational work in parallel with the tasks, which are assigned to hem by project manager. Moreover, this situation may have a negative influence on intermediate project results, and general to project itself, that`s why project manager try to find resources outside the company by creating virtual project team.
Keywords: Virtual teams; global projects team; project team manage-ment; Virtual teams classification